ANALISIS PRAGMATIK PADA PERCAKAPAN NOVEL “THE LONGEST RIDE BY NICHOLAS SPARKS”: PENDEKATAN PRAGMATIK - Ni Luh Warini; Ni Putu Elsa Sukma Dewi; Ni Nyoman Tri Sukarsih (LPPM Universitas Dhyana Pura, 2019)
ABSTRACTThis study aims at analyzing speech act related with stylistics theory at conversation in the novel entitled The Longest Ride by Nicholas Sparks. This study employs the descriptive qualitative method, while the data were taken by purposive sampling from the novel entitled “The Longest Ride by Nicholas Sparks”. The theory used is stylistics about literature of pragmatics. Stylistics is a linguistic approach to literature, explaining the relation between language and artistic function, with motivating questions (Leech, 1981). Besides that pragmatics is the study of speaker meaning (Yule, 1996). In pragmatics, there is implicit meaning, then called the speech act. The types of speech act used theory that proposed by Austin (1962) and Searle (1969). The findings of speech act from data at the novel consist of locutionary, illocutionary, perlocutionary speech act, and also directives, expressives, commissive.Keywords: Stylistics, pragmatics, speech acts, and novel.ABSTRAKPenelitian ini bertujuan untuk menganalisis tindak tutur yang terkait dengan teori stilistika pada percakapan dalam novel berjudul “The Longest Ride by Nicholas Sparks”. Penelitian ini menggunakan metode deskriptif kualitatif, sedangkan data diambil secara purposive sampling dari novel berjudul